Maritime History at the Crossroads : a Critical Review of Recent Historiography. - Broeze, Frank (Liverpool University Press, 2017)
This volume seeks to critically review the contemporary state of maritime historiography, as it stands at the volume's publication date of 1995.
Keywords: Merchant marine -- Historiography.; Navigation -- History -- Historiography.; Navigation -- History.; Marine marchande -- Historiographie.; Navigation -- Histoire.; History